Development and field testing of Geocomposite Cellular Mats (GCM) to minimize the ground movements of highway embankments founded on peat ground - Tuan Ismail, Tuan Noor Hasanah; Wijeyesekera, Devapriya Chitral; Bakar, Ismail (Springer, 2021)
Challenging grounds are often met in planning, design and construction of highway embankments which as a consequence succumb to undesirably excessive ground movements. Such ground conditions can range from unforeseen cavernous grounds to soft compressible organic soils of variable depths. Often alternate route planning is not feasible, and if necessary alternative construction procedures are not adopted, the net result will be unwanted roads user discomforts such as bumpy roads or even fatal road collapse. Highway constructions norms to circumvent such occurrences are to replace with alternative transported foundation soil/ground improvement or use an appropriate form of geo mats. Hence, this paper presents an alternative and innovative lightweight fill material: Geocomposite Cellular Mat (GCM) used to minimize the ground movements of highway embankments over peat ground. The conceptual development of a stiff mat structure but with a weight lighter than the embankment fill soil is described. The material used for the stiff mat is environmentally friendly in utilizing recycled plastic and its structure, enabling the free movement of water to dissipate any excessive porewater pressures. The performance of theGCMwas appraised under field trial conditions on a test site in Parit Nipah, Johor, Malaysia. The site comprised of a vast expanse of hemic peat and environmental conditions at the test site were fully monitored. The geotechnical properties of the peat at Parit Nipah were typically high organic matter content (~85%), high moisture content (>600%) and very low undrained shear strength (<15 kPa). Details of the set up and layout of the trial embankments tested are fully described, and the techniques adopted to get a comprehensive narrative of the settlement characteristics using innovative measurement techniques are also described. The performance of the GCM incorporated embankment was compared with that of a similar embankment that was formed of conventional backfill (sand fill). The findings show that the field ground movement observations confirmed that themaximum settlementswere reduced by up to 84% with the GCMfills.Moreover, the differential settlements were reduced by up to 70%.